Effects of joint designs on fracture toughness of the butt welds aluminium alloy 5052 / Dahia Andud - Andud, Dahia (2012)
This research was carried out to analysis the chemical composition, fracture mechanism and mechanical properties of the butt weld aluminium alloy 5052 that made with different joint design. Another aim was to correlate the impact strength and fracture toughness of the butt welds AA5052. The study was focused on experimental methodology. The results of the study were that the weld metal has a coarse grain structure which is harder compared with the HAZ that has a grain growth structure. The fracture surface of weld metal exhibit ductile fracture, while the HAZ implies mixed mode ductile fracture. The chemical weight percentage, ductility, tensile strength, fracture toughness and impact strength of the entire butt weld are dependable on the groove and bevel angle of the welded joint design. However, joint design does not influence the hardness of the entire butt welds AA5052 but influenced by the heat input of the welding. The correlation between impact toughness and fracture toughness was developed, however further works need to be conducted in order to obtain proper data for the correlation. The principal conclusion was that joint design has a significant effect on the chemical weight percentage and mechanical properties of the butt welds AA5052. However further works need to be conducted on the correlation between impact strength and fracture toughness.